Marketing scales handbook : multi-item measures for consumer insight research. - Bruner, Gordon C., 1954- (GCBII Productions, LLC, 2019)
This tenth volume in the long-running series has reviews 402 new consumer-related measurement scales that were reported in top marketing journal articles published in 2016 and 2017. Each review provides the scale items as well as information regarding the scale's origin, previous users, and measurement quality.